Risk Management Plan Infinity Workspace - Bakar, Lintang Abu; Indradewa, Rhian; Abadi, Ferryal; Iskandar, Muhammad Dhafi (Syntax Literate, 2025)
Hybrid and remote working models have become a major trend since the COVID-19 pandemic. This has created a growing demand for flexibility in the workplace. With the increasing demand for work flexibility, the growth of the startup economy, the adoption of hybrid work patterns, and the rising popularity and adoption of remote education, there is a significant opportunity for the establishment of Infinity Workspace (IWS) in Jakarta, which promises to become a reliable partner for professional workers, students, small and medium-sized enterprises (SMEs), startups, and corporations, while contributing to a sustainable and innovative business ecosystem. Porter’s Five Forces Analysis is used by IWS to analyze and identify external factors that may influence the company. Subsequently, IWS conducts an analysis using the VRIO (Valuable, Rare, Inimitable, Organized) framework to identify internal resources and capabilities that can serve as sources of competitive advantage for the company’s business sustainability. The Lean Canvas Model is also used by IWS to identify, eliminate, and minimize risks in product or business development. IWS provides flexible and innovative workspace solutions tailored to diverse user needs, targeting students and individuals, Small and Medium Enterprises (SMEs), startups, medium to large-sized companies, and content creators/podcasters. Investment feasibility analysis is conducted as a measure to assess the prospects of an investment project in decision-making regarding whether to accept or reject an investment. The ROI calculation for Infinity Workspace is positive. This indicates that Infinity Workspace will generate significant profits and can sustain the investment. Furthermore, the NPV calculation yields an NPV > 0, meaning it is predicted to generate profits and Infinity Workspace is viable to operate. The Payback Period (PP) calculation results in 1.84 years, equivalent to 1 year and 10 months. The IRR is 92%, concluding that the investment can proceed. Risk management is structured based on the ISO 31000:2018 standard to address potential risk events that may occur in the operations of Infinity Workspace.